HABITAT, DISTRIBUSI DAN STRUKTUR UKURAN IKAN OPUDI (Telmatherina antoniae) DI DANAU MATANO - Y. Tantu, Fadly; Sulistiono, Sulistiono; Muchsin, Ismudi (AgriSains, 2012)
Study on habitat, distribution and size structure of opudi (Telmatherina antoniae) was carried out in Lake Matano, South Sulawesi from September 2010 to August 2011. Habitat was described based on underwater observations. Fish collections were accomplished monthly by using beach seine. The fish was distributed throughout littoral areas within clear water. The observed habitat ranged between sandy, cobbles to bouldery bottom substrate. Some parts of habitat had less vegetation and the others did not. Fish collected during the study were 2707 individuals, in which 53.08% of them were males and the remains were females. The individuals had standard length (SL) ranged between 32.76 and 85.67 mm. Male specimens were dominated by individuals ranged between 41.58 and 54.80 mm (78.98% of total male specimens). Female specimens were dominated by individuals ranged between 37.17 and 54.80 (87.80% of total female specimens). Both male and female individuals were dominated by large size classes.Key words: Distribution,habitat, size structure, Telmatherina antoniae.